2001
DOI: 10.22358/jafs/70117/2001
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition and luminal degradability of maize silages depending on the cultivar and mowing height at harvest

Abstract: The experiment was designed in a bifactor model with five maize hybrids (Rasant, Dragon, LG 2252, San and Magister), mowed at two heights, i.e., 10-12 cm (A) and 50 cm (B). The average yield of dry matter of plants cut at a height of 50 cm (B) was 130.5 dt/ha and was significantly lower than the yield obtained from maize mowed at a height of 10-12 cm (A), where it amounted to 148.1 dt/ha. The percentage of ears showed the opposite trend, with 55.3 and 49.2%, respectively. Dry matter in all silages ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…In our lactation trial, DM yield was decreased by about 10% when height of cutting was increased. Pitzen (2000) and Kruczynska et al (2001) each compared DM yields at cut heights that were similar to those used by us and reported similar decreases in DM yield. Curran and Posch (2000) reported about a 12% decline in DM yield between cut heights that left 10.2 vs. 50 cm but only a 7% decline comparing cut heights of 20.4 vs. 50 cm.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In our lactation trial, DM yield was decreased by about 10% when height of cutting was increased. Pitzen (2000) and Kruczynska et al (2001) each compared DM yields at cut heights that were similar to those used by us and reported similar decreases in DM yield. Curran and Posch (2000) reported about a 12% decline in DM yield between cut heights that left 10.2 vs. 50 cm but only a 7% decline comparing cut heights of 20.4 vs. 50 cm.…”
Section: Discussionmentioning
confidence: 67%
“…Increasing the cutting height of whole-plant corn at harvest also improved its nutritive value for dairy cattle by reducing the concentrations of NDF, ADF, and ADL but increasing the concentrations of starch and in vitro NDF-D. Kruczynska et al (2001) also observed a reduction in crude fiber and ADF, and greater effective degradability of silage that was cut at 50 vs. 10 cm. Dominguez at al.…”
Section: Discussionmentioning
confidence: 88%
“…Neylon & Kung (2003) and Bernard et al (2004) evaluated the effect of corn plants cutting height in diets for dairy cows and observed that the increase in cutting height enhanced the nutritive value, reducing NDF and ADF, and increasing starch concentrations. Kruczynska et al (2001) also reported reduction of the fibrous fraction and increase of effective degradability of silages produced from plants cut at 50 cm, compared to the ones cut at 10 cm above ground.…”
Section: Resultsmentioning
confidence: 86%
“…The intake of MS increases with advanced maize crop maturity at harvest up to about 350 g DM kg -1 fresh sample, after which it decreases due to declining digestibility of starch and neutral detergent fibre (NDF) (Kruczyńska et Besides maturity, the cutting height also increases DM in MS due to a higher proportion of stover and grain in the forage (Kowalik and Michalski, 2006;Caetano et al, 2011), whereas the cutting height does not affect the DM content of the matured maize crop (< 400 g ST kg -1 fresh crops) (Neylon and Kung, 2003). With an increase in the cutting height of maize crop, there is a decrease in the content of NDF in MS and greater digestibility of fiber and DM in the digestive tract of ruminants (Curran i Posch 2000; Kruczyńska et al, 2001;Neylon and Kung, 2003;Kruczyńska et al 2011). Most changes in MS reported due to increased cutting height have been related to the fact that more fibrous and highly lignified stems are left in the field (Tolera and Sundstøl, 1999).…”
Section: The Effect Of Maize Crop Maturity and Cutting Height On Maiz...mentioning
confidence: 99%